THE ROLE OF ARTIFICIAL INTELLIGENCE IN HEALTHCARE MANAGEMENT - M. M. Muyassarova; S. E. Boltaboyev (Journals Park Publishing, 2025)
The emergence of artificial intelligence (AI) in healthcare has been groundbreaking, reshaping the way we diagnose, treat and monitor patients. This technology is drastically improving healthcare research and outcomes by producing more accurate diagnoses and enabling more personalized treatments. AI in healthcare’s ability to analyze vast amounts of clinical documentation quickly helps medical professionals identify disease markers and trends that would otherwise be overlooked. The potential applications of AI and healthcare are broad and far-reaching, from scanning radiological images for early detection to predicting outcomes from electronic health records. By leveraging artificial intelligence in hospital settings and clinics, healthcare systems can become smarter, faster, and more efficient in providing care to millions of people worldwide. Artificial intelligence in healthcare is truly turning out to be the future – transforming how patients receive quality care while mitigating costs for providers and improving health outcomes.